2019
DOI: 10.6004/jnccn.2018.7101
|View full text |Cite
|
Sign up to set email alerts
|

Low Provider Knowledge Is Associated With Less Evidence-Based Lung Cancer Screening

Abstract: Background: Despite widespread recommendation and supportive policies, screening with low-dose CT (LDCT) is incompletely implemented in the US healthcare system. Low provider knowledge of the lung cancer screening (LCS) guidelines represents a potential barrier to implementation. Therefore, we tested the hypothesis that low provider knowledge of guidelines is associated with less provider-reported screening with LDCT. Patients and Methods: A cross-sectional survey was performed in a large academic medical cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 26 publications
2
22
0
Order By: Relevance
“…In the VHA's demonstration project, only 57.7% of eligible Veterans agreed to be screened and reasons for declining screening are unknown (9). At the provider level, awareness of lung cancer screening and knowledge of the guidelines is also critical (14). Studies of VHA providers found that knowledge of the USPSTF guidelines and Centers for Medicare & Medicaid Services (CMS) coverage criteria is low (14,15), and providers who lack knowledge are less likely to perform screening (14).…”
Section: Discussionmentioning
confidence: 99%
“…In the VHA's demonstration project, only 57.7% of eligible Veterans agreed to be screened and reasons for declining screening are unknown (9). At the provider level, awareness of lung cancer screening and knowledge of the guidelines is also critical (14). Studies of VHA providers found that knowledge of the USPSTF guidelines and Centers for Medicare & Medicaid Services (CMS) coverage criteria is low (14,15), and providers who lack knowledge are less likely to perform screening (14).…”
Section: Discussionmentioning
confidence: 99%
“…Details of the questionnaire have been published elsewhere and are summarized here [ 22 ]. Between February and May 2017, we surveyed 625 healthcare providers across four specialties (General Internal Medicine, Pulmonology, Hematology/Oncology, and Gynecology) that are primarily responsible for preventive services (General Internal Medicine, Gynecology), care for patients with smoking-related lung disease (Pulmonology) or patients with a history of cancer (Hematology/Oncology) at two institutions (AHC and VHA) and included hospital-based and community-based practices.…”
Section: Methodsmentioning
confidence: 99%
“…61 Lack of CLTS knowledge may prevent PCPs from engaging in shared decision making (SDM) conversations with their patients. 62 A recent study reported that PCPs who are less familiar with the qualifying CTLS criteria had 2.7 times higher odds of ordering CXR than CTLS. 62 The Centers for Medicare & Medicaid Services (CMS) requires the use of a formal decision aid as part of CTLS SDM.…”
Section: Current Guidelines and Recommendations On Ctlsmentioning
confidence: 99%
“…62 A recent study reported that PCPs who are less familiar with the qualifying CTLS criteria had 2.7 times higher odds of ordering CXR than CTLS. 62 The Centers for Medicare & Medicaid Services (CMS) requires the use of a formal decision aid as part of CTLS SDM. 40 An accurate decision aid that is understandable to the general public is critical, and we provide an updated decision aid for use in clinics (Fig.…”
Section: Current Guidelines and Recommendations On Ctlsmentioning
confidence: 99%